Optimal Locations for Electric Vehicle Charging Stations using Flower Pollination Optimization - Yasin Z.M.; Aziz M.A.A.; Salim N.A.; Aziz N.F.A. (UiTM Press, 2023)
The deployment of electric vehicles has recently spread to many countries globally. This is due to their environmentally friendly nature and superior features compared to gasoline vehicles. Aside from being environmentally friendly, electric vehicles are also more efficient and have stable prices compared with gasoline vehicles. The increasing number of electric vehicle buyers has increased the demand for charging stations to cater to the need for electric vehicles. Therefore, charging stations should be optimally placed so that any electric vehicle users can conveniently access them. In this paper, the optimal placement of charging stations is proposed while ensuring that they are well distributed in all areas with minimum power and annual energy cost losses. Flower Pollination Optimization (FPO) is implemented in this paper to find the minimum power loss and annual energy cost loss by determining the best locations for the charging stations. FPO is a new technique for optimization which is based on the pollination behaviour of flowers. This behaviour consists of global pollination and local pollination processes. The proposed technique is validated using an IEEE-69 bus distribution test system. The results indicate that the FPO technique can be used to obtain the best location for charging stations with minimum power and annual energy cost losses as compared to other techniques 2021 College of Engineering, Universiti Teknologi MARA (UiTM), Malaysia